Zukunftsfähiges Umweltrecht I Umweltrecht im Anthropozän - Das Vorsorgeprinzip vor neuen Herausforderungen - Köck, Wolfgang; Markus, Till; Reese, Moritz (Leipziger Schriften zum Umwelt- und Planungsrecht, 2023)
This volume contains the first results of the research project "Challenges for a sustainable environmental law", which was started in summer 2020 on behalf of the Federal Environment Agency. The subject of the study is the challenges facing environmental law in the Anthropocene. The project approaches these challenges through a thorough review of the national and international legal literature on the tasks of environmental law in the Anthropocene, and it also focuses on the tasks and performance that the precautionary principle has or should have in the process of policy and legal development.